Contrast and font affect reading speeds of adolescents with and without a need for language-based learning support - Heiner Böttger; Julia Dose; Tanja Müller (Peoples' Friendship University of Russia (RUDN University), 2017)
This pre-study investigates the effects of the font type and the contrast between the colour of the text and the colour of the background on the reading speed of readers a) with different age groups and b) with a different need for language-based learning support using state-of-the art eye-tracking technology. We determine no significant difference between participants who were or were not receiving learning support (special support with a specialist teacher) due to language-based reading disabilities when reading the font type Open Dyslexic. This suggests that this font increases the reading speed of participants who receive learning support for language-based learning disabilities. Comparison of the reading speed for different passages of text displayed in different colour combinations indicates that a contrast of light text on a dark background may improve reading ability and reading performance. Both of these findings have significant implications for foreign-language teaching.